Draft Methodology to Specify the Railway Sections Capacity - Abramovic Borna; Zitricky Vladislav; Mesko Pavol (Logi, 2017)
This paper presents the individual parameters of the selected railway corridors in the selected country. Particularly, it describes the specific features of selected corridors in this country, summarizes their capacity, as well as proposes the methodology in order to specify the capacity of given railway section. The outcome is represented by the calculation of the appropriate railway section capacity implemented on the particular railway corridor in the selected EU country.